2014
DOI: 10.5560/znb.2014-4016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Novel Re(BIAN)(CO)3Cl Derivatives Including the First Example of a Water-soluble Tricarbonyl Rhenium(I) Complex with Bis(imino)acenaphthene Ligands

Abstract: A series of rhenium(I) carbonyl chloride complexes carrying bis(imino)acenaphthene (BIAN) molecules as p-acceptor ligands was prepared and characterized by various spectroscopic techniques. Among the novel compounds described, the remarkable example of a deeply colored water-soluble rhenium carbonyl derivative is presented. The crystal structures of this family of BIAN compounds are also reported, which confirm the position of the chloro ligand at the tricarbonyl rhenium(I) center. In the case of BIAN ligands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…[14, 27] The rhenium complex 1 was synthesized as previously reported. [14] General procedure for the preparation of 2 and 3 :[28] Equimolar amounts of Re(CO) 5 Cl (0.05 g, 0.14 mmol) and the corresponding bis(arylimino)acenaphtene ligand were refluxed in dry toluene (4 mL) for 30 min. Complete precipitation of the product was obtained upon cooling the reaction mixture to room temperature and slow addition of n -hexane.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[14, 27] The rhenium complex 1 was synthesized as previously reported. [14] General procedure for the preparation of 2 and 3 :[28] Equimolar amounts of Re(CO) 5 Cl (0.05 g, 0.14 mmol) and the corresponding bis(arylimino)acenaphtene ligand were refluxed in dry toluene (4 mL) for 30 min. Complete precipitation of the product was obtained upon cooling the reaction mixture to room temperature and slow addition of n -hexane.…”
Section: Methodsmentioning
confidence: 99%
“…[23] Electrochemical studies and product gas analysis up to now suggest that the reaction cycle of our new catalysts 2 and 3 proceeds in a similar way, and that the release of the chloro ligand might be directly influenced by the aryl group substituents of the BIAN-R ligands. [28]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although a few ionic transition metal carbonyl complexes are water-soluble, the CO release tests indicated that the M-CO bonds of simple ionic CO-RM degraded quickly under complicated physiological conditions and produced unpredictable side effects, such as blocking blood vessels and causing cytotoxic effects. Increasing the water-solubility and finely controlling the CO release kinetics of transition metal complexes are challenges in therapeutic CO-RMs [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that imines are electrochemically active in the presence of CO 2 [19], and that CO 2 electroreduction occurs as part of an inner sphere electron transfer mechanism [20]. Thus, more recent applications of BIAN ligands have looked into the ever growing field of CO 2 reduction, with Re(I)BIAN carbonyl complexes reported which catalysed a two-electron CO 2 photocatalytic reduction [21], as well as a Rh(III)BIAN complex which has shown CO 2 electrocatalytic reduction ability following its in situ reduction to the Rh(I) oxidation state [22,23]. Before these studies, Rh(I)BIAN complexes were reported as part of synthetic [24,25] or catalytic studies [26,27], while reactivity with the solvent acetonitrile complicated electrochemical analyses of the single five-coordinate complex previously reported [22,23].…”
Section: Introductionmentioning
confidence: 99%